2021
DOI: 10.4102/sajp.v77i1.1526
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative physical activity and functional performance levels are predictors of acute postoperative outcomes in a private South African colorectal cancer cohort

Abstract: Background: For patients with colorectal cancer, surgical resection of the primary tumour remains the best treatment option. Surgery for colorectal cancer is being performed on patients who would previously not have been considered as suitable candidates. It remains to be seen which factors influence hospital length of stay (LOS) and the development of acute postoperative complications in South African patients.Objectives: The objectives of our study were to determine the modifiable factors that influence pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
0
4
1
Order By: Relevance
“…Also ileostomies contain digestive juices which cause insult to the skin resulting in skin excoriation (21), and it's not surprising that they were the commonest complication seen. Contrary to our ndings, Whelan et al (23) in south Africa, reported that the commonest stoma complication was high output stoma representing 80% of all complications. This is possibly because they had a big number of patients with a short proximal length of jejunum and ileum left after placement of ileostomy, yet in our study, more than 90% of the participants had more than 3 meters of proximal jejunum and ileum left.…”
Section: Discussioncontrasting
confidence: 99%
“…Also ileostomies contain digestive juices which cause insult to the skin resulting in skin excoriation (21), and it's not surprising that they were the commonest complication seen. Contrary to our ndings, Whelan et al (23) in south Africa, reported that the commonest stoma complication was high output stoma representing 80% of all complications. This is possibly because they had a big number of patients with a short proximal length of jejunum and ileum left after placement of ileostomy, yet in our study, more than 90% of the participants had more than 3 meters of proximal jejunum and ileum left.…”
Section: Discussioncontrasting
confidence: 99%
“…36 Preoperative functional performance levels and physical activity are predictors of acute postoperative outcomes in South African patients undergoing colorectal cancer resection. 5 This supports the decision to include physical activity and information regarding other lifestyle-related factors to effect changes in acute and long-term outcomes in this patient group.…”
Section: Discussionmentioning
confidence: 54%
“…4 Emerging data from a cohort of patients from a private South African hospital have shown that surgical site infection and postoperative paralytic ileus were the most frequently reported postoperative complications in patients who underwent surgical resection for colorectal cancer. 5 Prehabilitation has been defined as the process of improving an individual's functional capacity to better withstand a stressful event such as surgery. 6 There is research supporting the use of preoperative exercise strategies to optimise overall health and improve postoperative outcomes in patients undergoing surgery for various forms of abdominal cancers.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that participants with MET 12 had lower risk for overall complications, but that this could not be explained by differences in any specific type of complications. Whelan et al recently reported results from a study on 125 patients with colorectal cancer in South Africa [12]. They reported an association between baseline physical activity and length of hospital stay, but not postoperative complications.…”
Section: Discussionmentioning
confidence: 99%